Adherence to Treatment by Initial Antihypertensive Mono and Combination Therapies. (26th May 2021) - Rea, Federico; Savaré, Laura; Franchi, Matteo; Corrao, Giovanni; Mancia, Giuseppe
Abstract: Background: Aim of our study was to compare adherence to antihypertensive drug therapy between newly treated patients in whom monotherapy or a 2-drug single-pill combination (SPC) was initially dispensed. Methods: The 63, 448 residents of Lombardy Region (Italy), aged 40–80 years, who were newly treated with antihypertensive drugs during 2016, were identified and followed for 1 year after the first prescription. The outcome of interest was adherence to drug therapy that was measured according to the "proportion of days covered" (PDC) criterion, i.e., the ratio between the number of days in which the drug was available and the days of follow-up. Patients who had a PDC >75% and <25% were defined as highly and poorly adherent to drug therapy, respectively. Log-binomial regression models were fitted to compare the propensity to treatment adherence between the initial therapeutic strategies, after adjusting for baseline demographic and clinical covariates. Results: About 46% and 17% of patients showed high and poor adherence, respectively. Compared with patients under initial monotherapy (85%), those who were initially treated with a SPC (15%) had higher propensity to be highly adherent and a lower propensity to be poorly adherent to antihypertensive treatment (risk ratio: 1.18, 95% confidence interval 1.16–1.21; 0.42, 0.39–0.45, respectively). This was the case regardless the sex, the age, the patient clinical status, and with almost any type of SPC. Conclusions: In a real-life setting, patients who were initially prescribed a 2-drug SPC exhibited more frequently a good adherence to antihypertensive treatment than those starting with a single drug. Graphical Abstract: